Alopecia mucinosa responding to antileprosy treatment: Are we missing something? - Rajiv Joshi; Vinay Gopalani (Wolters Kluwer Medknow Publications, 2013)
Three cases with single lesion of Alopecia mucinosa (follicular mucinosis) were treated with antileprosy treatment and showed rapid and complete resolution of the lesions with no recurrence on extended follow-up. Two children, a boy aged 14 years and a girl aged 12 years presented themselves, each, with a single hypopigmented, hypoesthetic patch on the face. Clinically leprosy was suspected, however, skin biopsy from both patients revealed follicular mucinosis as the only pathological finding, without any granulomas. Based on clinical suspicion both were started on multi drug therapy (MDT) for leprosy with complete resolution of the lesions. The third case, male, aged 22 years presented with a single erythematous, hypoesthetic plaque on the forehead.This lesion had been diagnosed as follicular mucinosis with folliculo-tropic mycosis fungoides, in the USA. He too responded completely within 3 months with rifampicin, ofloxacin, minocycline (ROM) treatment, which was given once monthly for a total of 6 months and remains free of disease since the past 1 year. Follicular mucinosis as the only pathology may be seen in facial lesions of clinically suspected leprosy in children and young adults. Based on histological findings these cannot be diagnosed as leprosy and will be considered as Alopecia mucinosa. These lesions, however, are always single and show rapid and complete response to antileprosy treatment. The authors suggest that in regions endemic for leprosy, such as India, single lesion Alopecia mucinosa on the face in children and young adults should be given antileprosy treatment.